Warning labels on alcoholic beverage containers: a pilot randomized experiment among young adults in Mexico - Nancy López-Olmedo; Karla Muciño-Sandoval; Francisco Canto-Osorio; Adriana Vargas-Flores; Alai Quiroz-Reyes; Arturo Sabines; Miguel Malo-Serrano; Sergio Bautista-Arredondo; MArantxa Colchero; Tonatiuh Barrientos-Gutiérrez (BMC, 2023)
Abstract Background Little is known about the potential impacts of visible and up-to-date health warning labels on alcoholic beverage containers on a range of outcomes in low- and middle-income countries. We conducted an experimental study to test the potential impacts of visible health warning labels (on the principal panel of the package) on thinking about health risks, product attractiveness, visual avoidance, and intention to change alcohol use among students in Mexico aged 18-30 years. Methods A double-blind, parallel-group, online randomized trial was conducted from November 2021 to January 2022 in 11 states in Mexico. In the control group, participants were presented with the image of a conventional beer can with a fictional design and brand. In the intervention groups, the participants observed pictograms with a red font and white backgrounds (health warning label in red-HWL red) or with a black font and yellow backgrounds (health warning label in yellow-HWL yellow), located at the top, covering around one-third of the beer can. We used Poisson regression models -unadjusted and adjusted for covariates- to assess differences in the outcomes across study groups. Results Using intention-to-treat analysis (n = 610), we found more participants in groups HWL red and HWL yellow thought about the health risks from drinking beer compared to the control group [Prevalence Ratio (PR) = 1.43, CI95%:1.05,1.93 for HWL red; PR = 1.25, CI95%: 0.91, 1.71 for HWL yellow]. A lower percentage of young adults in the interventions vs control group considered the product attractive (PR 0.74, 95%CI 0.51, 1.06 for HWL red; PR 0.56, 95%CI 0.38, 0.83 for HWL yellow). Although not statistically significant, a lower percentage of participants in the intervention groups considered buying or consuming the product than the control group. Results were similar when models were adjusted for covariates. Conclusions Visible health warning labels could lead individuals to think about the health risks of alcohol, reducing the attractiveness of the product and decreasing the intention to purchase and consume alcohol. Further studies will be required to determine which pictograms or images and legends are most contextually relevant for the country. Trial registration The protocol of this study was retrospectively registered on 03/01/2023: ISRCTN10494244.